EasyMark: Semiautomatic Image Annotation Tool - Vargas, Samuel S.; Santos, João P. S. dos; Silveira, Thiago L. T. da; Lunardi, Gabriel M.; Oliveira, Adriano Q. de (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS); 2025: Anais da I Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região SulDO - 10.5753/eramiars.2025.16754, 2025)
Image annotation tools are indispensable in this era of rapid Artificial Intelligence (AI) development, where image inference systems can be applied in most fields to aid professionals in several tasks. However, the current solutions are found to be lacking in multiple areas, including access, availability, security, and trust. For these reasons, this project aims to develop EasyMark, an image annotation tool designed to address these pressing issues, aiming for the safety and privacy of its users. At its current state, EasyMark is capable of manually and automatically annotating image folders, while remaining fully offline and open-source.